Modulating the activity of the channel-forming segment of Vpr protein from HIV-1 - Chen, Chin-Pei; Kremer, Clemens; Henklein, Peter; Schubert, Ulrich; Fink, Rainer; Fischer, Wolfgang B. (European biophysics journal, 2010)
Viral protein of regulation (Vpr) encoded by human immunodeficiency virus type 1 (HIV-1) is a short auxiliary protein that is 96 amino acids in length. During the viral life cycle, Vpr is released into the blood serum and is able to enter cellular membranes of noninfected cells. In this study a short peptide, Vpr55-83, was shown to exhibit ion-channel-like activity when reconstituted into (1) planar lipid bilayers and (2) lipid bilayers held at the tip of a glass pipette. The two set-ups led to differences in the oligomerization state of the peptide, which was reflected in differences in the conductance levels. Experiments under applied hydrostatic pressure affect the dynamics of the protein within the membrane.